IMPROVING THE METHODOLOGY OF USING CONNOTATIVE TEACHING MATERIALS IN PRACTICAL ENGLISH COURSES - Dilnoza Rixsiboyevna Xoshimova (Western European Studies, 2024)
The main essence of the scientific research is to improve the teaching of foreign languages in the higher education system using connotative materials.
Keywords: connotative; denotative